The Relationship of Liver and Pancreas Density With Chest Computed Tomography Score Progression and Laboratory Findings in Patients With COVID-19 - Gul, Yeliz; Kilicarslan, Gulhan; Cilengir, Atilla Hikmet; Balaban, Mehtap; Gul, Evrim (Lippincott Williams & Wilkins, 2022)
ObjectiveAbdominal involvement of COVID-19 is a current issue. We aimed to evaluate hepatic and pancreatic density alterations on computed tomography (CT) and to analyze whether these alterations had a relationship with chest CT score and laboratory findings.MethodsPatients with reverse transcription-polymerase chain reaction-confirmed COVID-19 from March 11, 2020, to February 6, 2021, were retrospectively analyzed. Patients were divided into nonprogressive and progressive groups according to their chest CT scores. Liver and pancreas density, and liver-to-spleen (L/S) ratio were calculated. Laboratory findings, medication, intensive care unit stay, and survival were noted.ResultsThere were 51 patients in the nonprogressive group and 123 patients in the progressive group. The median (minimum to maximum) L/S value of the nonprogressive group was 1 (0.28-1.53) at admission and 1.06 (0.33-1.83) at follow-up (P < 0.001). In the progressive group, the median L/S value was 1.08 (0.35-1.51) at admission and 0.92 (0.33-1.75) at follow-up (P < 0.001). A significant difference was found between the 2 groups at admission and follow-up (P = 0.010 and P < 0.001, respectively). Pancreatic density measured at follow-up was significantly lower in the progressive group (P = 0.045). In the progressive group, aspartate aminotransferase, total bilirubin, creatinine, urea, C-reactive protein, D-dimer, and white blood cell values were higher; albumin and lymphocyte values were lower (P < 0.05).ConclusionsPatients with COVID-19 with progressive CT scores may have a decrease in L/S values, and their pancreatic density is lower than nonprogressives. Aspartate aminotransferase, total bilirubin, creatinine, urea, C-reactive protein, D-dimer, and white blood cell values tend to be higher in patients with a high chest CT score.
Keywords: computed tomography; coronavirus; density; liver; pancreas